Tissue‐specific responses to aberrant FGF signaling in complex head phenotypes1. Issue 1 (5th December 2012) - Martínez‐Abadías, Neus; Motch, Susan M.; Pankratz, Talia L.; Wang, Yingli; Aldridge, Kristina; Jabs, Ethylin Wang; Richtsmeier, Joan T.
Abstract BACKGROUND: The role of fibroblast growth factor and receptor (FGF/FGFR) signaling in bone development is well studied, partly because mutations in FGFRs cause human diseases of achondroplasia and FGFR‐related craniosynostosis syndromes including Crouzon syndrome. The FGFR2c C342Y mutation is a frequent cause of Crouzon syndrome, characterized by premature cranial vault suture closure, midfacial deficiency, and neurocranial dysmorphology. Here, using newborn Fgfr2cC342Y/+ Crouzon syndrome mice, we tested whether the phenotypic effects of this mutation go beyond the skeletal tissues of the skull, altering the development of other non‐skeletal head tissues including the brain, the eyes, the nasopharynx, and the inner ears. RESULTS: Quantitative analysis of 3D multimodal imaging (high‐resolution micro‐computed tomography and magnetic resonance microscopy) revealed local differences in skull morphology and coronal suture patency between Fgfr2cC342Y/+ mice and unaffected littermates, as well as changes in brain shape but not brain size, significant reductions in nasopharyngeal and eye volumes, and no difference in inner ear volume in Fgfr2cC342Y/+ mice. CONCLUSIONS: These findings provide an expanded catalogue of clinical phenotypes in Crouzon syndrome caused by aberrant FGF/FGFR signaling and evidence of the broad role for FGF/FGFR signaling in development and evolution of the vertebrate head. Developmental Dynamics 242:80–94, 2013. © 2012 Wiley Periodicals, Inc.